(untitled) (Journal of Enam Medical College, 2016)
Background: Considering safe treatment modalities for children with vitiligo, search for newer therapeutic agents continues. Hence, new immunomodulatory agents such as calcineurinantagonists, frequently referred to as topical immunomodulators (TIMs) have recently been introduced as new promising tools to treat acquired hypopigmentary disorders. Tacrolimus is safe in treating children due to lack of skin atrophy and less data are available on effect of topical tacrolimus on vitiligo. Objective: To see the effect of topical tacrolimus on vitiligo in children. Materials and Methods: This prospective study was done in outpatient department of Dermatology and Venereology, Chittagong Medical College Hospital (CMCH), Bangladesh. Clinically diagnosed vitiligo patients of up to 12 years age visiting Skin & VD OPD, CMCH during study period were the study population (total 30). The study was carried out from November 2007 to April 2008. Results: A total of 30 patients, 13 (43.33%) males and 17 (56.66%) females with focal, segmental or generalized vitiligo were studied. Seventy percent of study subjects were from 712 years of age. Topical tacrolimus 0.03% ointment was administered twice daily for 12 weeks to each patient. Repigmentation was complete (>75%) in 43.33% cases (13/30), was moderate (5075%) in 33.33% (10/30), mild (<50%) in 13.33% (4/30). Clinical adverse effects were noted in 6.67% (2/30) of cases where pruritus was in 3.33% (1/30) and burning in 3.33% (1/30). None of the reactions was severe, all were mild and well-tolerated and most occurred within the first month of initiation of treatment and resolved with continued use of drug and completely cured after the treatment completed. Nobody had to discontinue the therapy for side effects. Conclusion: In conclusion, tacrolimus ointment may be a rapidly efficacious and safe option for the treatment of vitiligo in children. The ease of topical self-administration with minimal side effects makes this novel immunomodulatory agent a promising addition to the therapeutic armamentarium for vitiligo in children. J Enam Med Col 2016; 6(1): 33-37